HUBUNGAN PATRON KLIEN DIANTARA MASYARAKAT NELAYAN DI DESA KANGKUNAWE KECAMATAN MAGINTI KABUPATEN MUNA BARAT PROVINSI SULAWESI TENGGARA - Sufirudin, _ (Universitas Sam Ratulangi, 2016)
Geographically Indonesia is the state of the islands lib reached 70 percent of the total territory. Thus the condition of the sea being thus broad accompanied wealth of natural resources so big, in fact Indonesia has not been able to become a developed. One of the problem is business player fisheries which is still dominated by traditional fishermen. Community fishermen is part of one the Indonesian people which lives with the potential resources manage fisheries. In general, the fishermen still experienced technology limitations arrest operation so that the region has become limited, only around coastal waters. In addition, dependency on very high season and not every moment can fishermen at the sea, especially on the season the waves, that lasts more than one month. This research aims to understand how the patron client relationship between community fishermen in the village of Kangkunawe. This research methodology using qualitative approach, and the collection technique or data processing in this research namely by means of observation / observation, interview / the interview, and documentation. This research result showed that the relationship between boss with fishermen tolerably good because between boss with fishermen pulling helping and mutually beneficial, and between boss with fishermen never happened conflict. Keywords: fishermen, coastal, patron client